2022
DOI: 10.1186/s40104-022-00742-y
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant procyanidin B2 protects oocytes against cryoinjuries via mitochondria regulated cortical tension

Abstract: Background Irreversible cryodamage caused by oocyte vitrification limited its wild application in female fertility preservation. Antioxidants were always used to antagonist the oxidative stress caused by vitrification. However, the comprehensive mechanism underlying the protective role of antioxidants has not been studied. Procyanidin B2 (PCB2) is a potent natural antioxidant and its functions in response to vitrification are still unknown. In this study, the effects of PCB2 on vitrified-thawed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 92 publications
0
9
0
Order By: Relevance
“…Procyanidin B2 is a potent natural antioxidant exhibiting multiprotective roles in response to vitrification stimuli. 43 In T. cuspidata , Procyanidin B2 was detected in vascular bundle cells and mesophyll cells. Additionally, bisdemethoxycurcumin and dimethylfraxetin were also significantly accumulated in the vascular system of T. cuspidata leaves ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Procyanidin B2 is a potent natural antioxidant exhibiting multiprotective roles in response to vitrification stimuli. 43 In T. cuspidata , Procyanidin B2 was detected in vascular bundle cells and mesophyll cells. Additionally, bisdemethoxycurcumin and dimethylfraxetin were also significantly accumulated in the vascular system of T. cuspidata leaves ( Figure 5 ).…”
Section: Resultsmentioning
confidence: 98%
“…cuspidata, isocolumbin and gartanin are two vascular bundle cell specifically accumulated active compounds (>90%), suggesting their movement between plant tissues. Procyanidin B2 is a potent natural antioxidant exhibiting multiprotective roles in response to vitrification stimuli . In T.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, we investigated the calcium levels in oocytes. A previous study showed that Rhod 2-AM and Fluo 4-AM could accurately track mitochondria Ca 2+ ([Ca 2+ ] m ) and endoplasmic reticulum Ca 2+ ([Ca 2+ ] ER ) in oocytes, respectively [ 27 ]. We also utilized Fluo 3-AM to analyze the cytoplasmic calcium ([Ca 2+ ] c ) concentration.…”
Section: Resultsmentioning
confidence: 99%
“…GSH acts as a natural antioxidant inside cells to inhibit oxidative stress ( Adeoye et al, 2018 ). Many studies have reported that ROS, GSH and MMP were indicators of oxidative stress on oocytes ( Zhuan et al, 2022 ; Bai et al, 2023 ; Sun et al, 2023 ). To further evaluate the effect of PLGA-RES on oxidative stress, ROS, GSH and MMP levels were measured, and the results indicated that PLGA-RES dramatically reduce oxidative status in in vitro matured oocytes.…”
Section: Discussionmentioning
confidence: 99%